2022
DOI: 10.3171/2021.11.peds21207
|View full text |Cite
|
Sign up to set email alerts
|

Temporosylvian arachnoid cysts in children. Part 2: Postoperative neuropsychological and clinical improvement

Abstract: OBJECTIVE The authors’ objective was to study clinical, imaging, and neuropsychological changes in children who underwent surgery for a temporal arachnoid cyst (TAC). METHODS Thirty-four children were prospectively assessed similarly at diagnosis and postoperatively (mean 14 months) with clinic visits, images, cognitive tests, and parental questionnaires on mood/behavior and executive functions. The scores were compared pre- and postoperatively for the entire cohort and individually. The scores of 25 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Controversy remains regarding the management and treatment of SFACs, speci cally regarding the role of surgical intervention for patients with relatively minor presentation. Although it remains controversial, several authors recommend cyst fenestration for asymptomatic SFAC because of improved cyst size reduction and low risk of complications [7,32] and improved neuropsychological disorders [10]. The complication rates presented in this report were low and cranial nerve de cits (3rd and 4th nerve) were transient and resolved spontaneously.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Controversy remains regarding the management and treatment of SFACs, speci cally regarding the role of surgical intervention for patients with relatively minor presentation. Although it remains controversial, several authors recommend cyst fenestration for asymptomatic SFAC because of improved cyst size reduction and low risk of complications [7,32] and improved neuropsychological disorders [10]. The complication rates presented in this report were low and cranial nerve de cits (3rd and 4th nerve) were transient and resolved spontaneously.…”
Section: Discussionmentioning
confidence: 67%
“…However, others reported less seizure control [7]. Cuny et al reported neuropsychychological testing before and after cyst fenestration showed improvement in 76% of 34 children [10]. They observed the rounded, convex shape of the cyst being more compressive and deleterious.…”
Section: Surgical Indicationmentioning
confidence: 99%
See 2 more Smart Citations
“…The presentation of ruptured SACs is mainly characterized by worsening raised ICP symptoms in a previously asymptomatic patient, often with apparently normal neuropsychological development [60,139]. Typically, raised ICP occurs some hours/days or even weeks after the injury (time necessary for the subdural collection formation) [11,13].…”
Section: Clinical Aspectsmentioning
confidence: 99%